Simulation for water quality management using system dynamics modeling in the Bedadung Watershed, East Java, Indonesia - Hendra Andiananta Pradana; Elida Novita; Bambang Herry Purnomo (Journal of Degraded and Mining Lands Management, 2022)
The potential for pollution of rivers is influenced by river-water discharge and the distribution of pollution sources. This research aimed to examine recommendations for water quality management in the Bedadung River segment of the Patrang, Sumbersari, and Kaliwates Districts as an urban area of Jember Regency refer to simulations of the total pollution load capacity for 10 years (2016-2026) using a system dynamics modeling. The preparation of a system dynamics modeling used Powersim 5.0 software. It could represent holistic environmental management modeling. The input data were total suspended solid (TSS), biochemical oxygen demand (BOD), chemical oxygen demand (COD) and the streamflow of the Bedadung River. The model scenarios were the business of usual, moderate, and optimistic scenarios involving environmental and socio-economic aspects. The medium-term and long-term recommendations for water quality management of the Bedadung River based on system dynamics simulation were respectively moderate scenario and optimistic scenario. The strategies of the moderate scenario were application of the best management practice method in agricultural cultivation, improving sanitation and domestic wastewater treatment, implementing clean production in the field of livestock and industry, as well as waste management on riverbanks. These alternative strategies for river water quality management can be used as consideration for protecting surface water sources in urban areas.